2009
DOI: 10.1021/jm801507v
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent, Selective, and Orally Efficacious Pyrimidinooxazinyl Bicyclooctaneacetic Acid Diacylglycerol Acyltransferase-1 Inhibitor

Abstract: Inhibition of DGAT-1 is increasingly seen as an attractive mechanism with the potential for treatment of obesity and other elements of the metabolic syndrome. We report here a bicyclooctaneacetic acid derivative in the pyrimidinooxazine structural class of DGAT-1 inhibitors that has good potency, selectivity, and pharmacokinetic characteristics across a variety of species. This compound is an effective inhibitor of DGAT-1 in both intestinal and adipose tissue, which results in a reduction in body weight or bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 18 publications
9
94
0
Order By: Relevance
“…Pharmacological or dietary factors capable of inhibiting intestinal DGAT1 activity specifically may thus be benefi cial for reducing obesity and hepatic steatosis. In fact, several DGAT1 inhibitors have shown effects on the intestine and dietary fat absorption (40)(41)(42).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Pharmacological or dietary factors capable of inhibiting intestinal DGAT1 activity specifically may thus be benefi cial for reducing obesity and hepatic steatosis. In fact, several DGAT1 inhibitors have shown effects on the intestine and dietary fat absorption (40)(41)(42).…”
Section: Downloaded Frommentioning
confidence: 99%
“…These findings suggest and encourage our exploration of novel DGAT-1 inhibitors, since pharmacological inhibition of DGAT-1 may be a feasible therapeutic strategy for human obesity and type 2 diabetes. Recent studies [7][8][9] have demonstrated that small molecule DGAT-1 inhibitors (I, II) showed the similar antiobesity effects previously demonstrated in DGAT-1 deficient mice. Both of compounds (I, II) have a similar linear structure with a terminal carboxylic acid group.…”
mentioning
confidence: 85%
“…Subsequent experiments using selective inhibitors of microsomal triglyceride transfer protein (MTP) in mice and DGAT1 in nonhuman primates highlight the utility of this approach to assess perturbations in lipid assembly resulting from pharmacological intervention. Comparability between treated and control groups in labeling of the precursor pool is demonstrated for each experiment, allowing the specifi city was obtained when the fragment ion selected for quantitation preserved the 13 C label (enhanced discrimination against isobaric chemical interferences).…”
Section: Experiments 2 Intravenous Administration Of Isotope: Effect mentioning
confidence: 99%
“…On the morning of study, overnight-fasted animals were treated with vehicle (20% TPGS) or one of two doses of DGAT1 inhibitor (0.3 and 3.0 mg/ kg) ( 13 ), with the solution mixed into a yogurt treat for conscious dosing 1 h prior to tracer administration. …”
Section: Experiments 3 Effect Of a Dgat1 Inhibitor On Distribution Ofmentioning
confidence: 99%
See 1 more Smart Citation